2023
DOI: 10.3389/fimmu.2022.1077335
|View full text |Cite
|
Sign up to set email alerts
|

The roles of fungus in CNS autoimmune and neurodegeneration disorders

Abstract: Fungal infection or proliferation in our body is capable of initiation of strong inflammation and immune responses that result in different consequences, including infection-trigged organ injury and inflammation-related remote organ dysfunction. Fungi associated infectious diseases have been well recognized in the clinic. However, whether fungi play an important role in non-infectious central nervous system disease is still to be elucidated. Recently, a growing amount of evidence point to a non-negligible role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 116 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…RTL9 is a promising antifungal therapy target as a newly identified member of innate antifungal immunity in eutherians. Furthermore, fungal infections in patients with Alzheimer's disease (AD) have been reported [40][41][42], suggesting that fungal infection may also be involved in the etiology of AD and/or other neurodegenerative diseases and non-infectious autoimmune diseases, such as multiple sclerosis, neuromyelitis optica, amyotropic lateral sclerosis and Parkinson's disease [40][41][42][43][44][45][46][47]. Recent studies on innate and adaptive immunity have reported that phagocytic cells are essential players in protecting against fungal diseases and that defects in these cells compromise the host's ability to resist fungal infection [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…RTL9 is a promising antifungal therapy target as a newly identified member of innate antifungal immunity in eutherians. Furthermore, fungal infections in patients with Alzheimer's disease (AD) have been reported [40][41][42], suggesting that fungal infection may also be involved in the etiology of AD and/or other neurodegenerative diseases and non-infectious autoimmune diseases, such as multiple sclerosis, neuromyelitis optica, amyotropic lateral sclerosis and Parkinson's disease [40][41][42][43][44][45][46][47]. Recent studies on innate and adaptive immunity have reported that phagocytic cells are essential players in protecting against fungal diseases and that defects in these cells compromise the host's ability to resist fungal infection [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that fungi may play an important role in the pathogenesis of MS [ 14 ] and the finding that genes involved in innate immunity are associated with the disease suggests a link between MS and dysregulation of the innate immune system [ 18 ].…”
Section: Msmentioning
confidence: 99%
“…Fungal toxins could have a direct role in the development of the disease by damaging oligodendrocytes and astrocytes, but the peripheral action of fungi on the immune system may also make a contribution [ 14 , 133 ].…”
Section: Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the study of fungal footprints in neurological diseases has the potential to contribute to our understanding of the underlying mechanisms of these conditions and may ultimately lead to improved strategies for prevention and treatment (Forbes et al, 2019). In particular, research has focused on the role of fungal infections in promoting inflammation and the production of misfolded proteins, which can contribute to the development of neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease (Wu et al, 2023).…”
Section: Fungal Footprintsmentioning
confidence: 99%